Hyperexponential model of token bucket system - Smiesko, Juraj (Communications - Scientific letters of the University of Zilina, 2004)
In the present paper we apply the Theory of Markov Chains for a formal description of a hyperexponential model of Token Bucket System (TBS). This paper extends the topic covered in [3] by replacing Exponential model of human speech by a more precise hyperexponential model. In the first section we deal with analysis of the Hyperexponential model of On-Off Source of human speech. In the second section we deal with steady-state analysis of Token Bucket system and we solve the balance equations for probabilities of states. In the third section we use real parameters of VoIP and we calculate characteristic of TBS and in the last section the values of probability of packet loss are approximated by an exponential regression function. We can directly compute values of probability of packet loss using this exponential function.